‘Professional’ Handball Education and Practice in Ethiopia : Review of Related Literature - HUNDITO, BIRUK (IJRDO - Journal of Social Science and Humanities Research, 2016)
Despite the assumption that students are being prepared as ‘professionals’, little debate has been undertaken concerning the composition of ‘professional’ handball education in Ethiopia. This paper comments upon this absence of serious debate and seeks first of all, to review accepted perspectives of professions and professionals, and secondly, to consider the changes that may need to be applied in the contemporary setting, and finally, to reflect upon the implications of this definition for handballeducation in Ethiopia . The paper concludes that a definition which encompasses occupation, competency and behavior also reveals several weaknesses in the conventional Ethiopian curriculum, including limited common standards and an almost complete absence of ethical codes.